Analysis of Factors Affecting Brand Loyalty: A Study of Coca-Cola - Ling, Gan Yu; Yuang, Gao; Zhicheng, Gao; Xuan, Gisele Tok Xuan; Maharani, Cevira Dewi; Genira, Chika Felsia; Tyagi, Nishita; M., Saidhanyakumar (AIBPM Publisher, 2023)
Every day, Coca-Cola beverages are consumed in more than 200 countries with more than 1.9 billion servings. This study is carried out with the aim to observe how Coca-Cola gains strong brand loyalty through factors including product quality, brand image, product design and product promotion. The goal of this study is to examine which is the most effective approach to attract and connect with consumers which leads to strong brand loyalty. The primary data of this research is collected from 150 respondents through online surveys via Google Form. Secondary data is also used to support this study. The result shows that health benefits, product quality, and product promotion influence the most on brand loyalty of the consumer to the Coca-Cola company. Suggestions for improvement and consequences are discussed in this paper.